Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.21273/horttech.13.1.0166
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Spraying in Indian River Grapefruit: II. Overview of Factors Influencing Spray Efficacy and Off-target Deposition

Abstract: Foliar application of spray materials is an integral component of commercial citrus production. An intensive assessment of spray application practices has been stimulated by low fruit value and increased concern about potential surface water contamination in the Indian River citrus region of Florida. Many publications report research results regarding distribution of spray materials within orchards and off-target deposition, but interpretation is challenging because so many factors influence spray resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 21 publications
0
23
0
3
Order By: Relevance
“…In general, it was observed that increase in the spray application volume increased the mean coverage and distribution uniformity in the canopy. Differences in coverage were only statistically significant in certain cases and at different locations inside the canopy, which could be caused by differences in foliar density, canopy size and pruning . The lowest values of coverage were always found at the top of the canopy, showing that this was the most difficult area for the operators to treat.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, it was observed that increase in the spray application volume increased the mean coverage and distribution uniformity in the canopy. Differences in coverage were only statistically significant in certain cases and at different locations inside the canopy, which could be caused by differences in foliar density, canopy size and pruning . The lowest values of coverage were always found at the top of the canopy, showing that this was the most difficult area for the operators to treat.…”
Section: Discussionmentioning
confidence: 91%
“…In the case of scales, which are sessile in many of their development stages, it has been stated that adequate control requires a threshold concentration of the appropriate pesticide on the surface of susceptible tissues. 38 In the present authors' opinion, divergences in the results reported in the literature demonstrate the need to conduct particular studies of each set of pests, pesticides, application methods and agricultural ecosystems to obtain conclusions for dose adjustments that could be reasonably generalised.…”
Section: Introductionmentioning
confidence: 86%
“…The temperatures and relative humidity were similar on both application dates, ranging from 25 to 30°C and 51 to 92%, respectively (Table 1). Other factors that could affect drift include canopy geometry and density in the area where targets were deployed, the design and setup of the sprayer, the types and orientation of nozzles, operating pressures, manufacturers, and technician‐controlled operational practices [18]. The interrelationships between all of these factors are sufficiently confounding that attributing differences in deposition results to any one element by itself is extremely difficult [19].…”
Section: Resultsmentioning
confidence: 99%
“…Deposition on the soil underneath trees was directly proportional to the volume applied, which is influenced by the mobility of the pest to be controlled (i.e., less thorough coverage needed to control mobile vs nonmobile pests) [20]. Others reported that the percentage of material drifting off‐site increases with both wind speed and decreasing droplet size, and ground surface deposits typically are greatest within 15 m of the sprayer [18]. The Spray Drift Task Force reported in 1997 (http://www.agdrift.com) that pesticide losses from drift and ground deposition ranged from less than 0.5 to 4% of the amount applied to tree orchards, including citrus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation